OPTIMIZATION OF REHABILITATION MEASURES IN CHILDREN WITH RECURRENT FORMS OF BRONCHITIS IN AN OUTPATIENT SETTING - Zakirova, U.I.; Maksudova, L.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Among the children of the city of Tashkent relapses of bronchial diseases are widespread. Therefore, in outpatient conditions in the complex treatment of such patients need timely and comprehensive therapeutic rehabilitation measures that increase the body’s defenses. Optimization of rehabilitation measures in children with recurrent forms of bronchitis includes the implementation of the basic principles of medical rehabilitation: 1. the earliest possible start of rehabilitation treatment-continuity and phasing of rehabilitation activities; 2. Complex character of medical, social, psychological and other measures; 3. Individual approach to the preparation of rehabilitation programs taking into account the course of the process, age, conditions and lifestyle of the sick child.